Argatroban in heparin-induced thrombocytopenia: rationale for use and place in therapy. (November 2013) - Bambrah, Ramandeep K.; Pham, Dat C.; Rana, Fauzia
Heparin-induced thrombocytopenia (HIT) is a recognized complication of heparin and requires urgent detection and treatment. HIT can be divided into two types, type I and type II, with type I being a transient decrease in platelet count without clinical consequence. For the purpose of this review, the term HIT refers to the immune-mediated type II that causes paradoxical thrombo-emboli. The aim of this review is to familiarize clinicians with a specific direct thrombin inhibitor, argatroban, in the treatment of HIT. Argatroban has been successfully employed in treating HIT in many different subsets of patients, including those with endstage renal disease on hemodialysis and in patients undergoing percutaneous coronary intervention and those with multiorgan dysfunction syndrome.